Prevalence of Work-Related Respiratory Symptoms in Iranian Farmers - N Hashemi; M Mirsadraee; MT Shakeri; AR Varasteh (Canadian Respiratory Journal)
BACKGROUND: Animal exposure may be an important trigger for work-related symptoms among farmers.